Mathematics
Kimberlyconnelly
2021-07-22 03:25:42
Solve. 3=-(-y+6) a. –9 b. –3 c. 3 d.
ANSWERS
candacerutledge
2021-07-22 10:06:31

3 = -(-y + 6) First, simplify the brackets. / Your problem should look like: 3 = y - 6 Second, add 6 to both sides. / Your problem should look like: 3 + 6 = y Third, add 3 + 6 to get 9. / Your problem should look like: 9 = y Fourth, switch the side. / Your problem should look like: y = 9 Answer: y = 9

edepinalondono
2021-07-22 10:07:46

3=−(−y+6) Simplify: 3=−(−y+6) 3=y+−6(Distribute) 3=y−6  Flip the equation. y−6=3  Add 6 to both sides. y−6+6=3+6 y=9

ADD ANSWER